A protocol developing, disseminating and implementing a core outcome set for infertility. Issue 3 (15th June 2018) - Duffy, J M N; Bhattacharya, S; Curtis, C; Evers, J L H; Farquharson, R G; Franik, S; Khalaf, Y; Legro, R S; Lensen, S; Mol, B W; Niederberger, C; Ng, E H Y; et al.
Abstract: STUDY QUESTIONS: We aim to produce, disseminate and implement a core outcome set for future infertility research. WHAT IS KNOWN ALREADY: Randomized controlled trials (RCTs) evaluating infertility treatments have reported many different outcomes, which are often defined and measured in different ways. Such variation contributes to an inability to compare, contrast and combine results of individual RCTs. The development of a core outcome set will ensure outcomes important to key stakeholders are consistently collected and reported across future infertility research. STUDY DESIGN, SIZE, DURATION: This is a consensus study using the modified Delphi method. All stakeholders, including healthcare professionals, allied healthcare professionals, researchers and people with lived experience of infertility will be invited to participate. PARTICIPANTS/MATERIALS, SETTING, METHODS: An international steering group, including people with lived experience of infertility, healthcare professionals, allied healthcare professionals and researchers, has been formed to guide the development of this core outcome set. Potential core outcomes have been identified through a comprehensive literature review of RCTs evaluating treatments for infertility and will be entered into a modified Delphi method. Participants will be asked to score potential core outcomes on a nine-point Likert scale anchored between one (not important) and nine (critical). Repeated reflection and rescoring should promote convergence towards consensus 'core' outcomes. We will establish standardized definitions and recommend high-quality measurement instruments for individual core outcomes. STUDY FUNDING/COMPETING INTEREST(S): This project is funded by the Royal Society of New Zealand Catalyst Fund (3712235). BWM reports consultancy fees from Guerbet, Merck, and ObsEva. R.S.L. reports consultancy fees from Abbvie, Bayer, Fractyl and Ogeda and research sponsorship from Ferring. S.B. is the Editor-in-Chief of Human Reproduction Open. The remaining authors declare no competing interests.